Konsep inovasi pendidikan dalam membentuk masyarakat madani di era disrupsi dan society 5.0 - Romadhoni, Nailil Izzah (Maliki Interdisciplinary Journal, 2026)
Technological developments in the era of disruption and Society 5.0 have created various challenges for the education sector, including low digital, literacy, reduced social interaction, declining, moral values, and the increasing demand for 21st-century skills. These conditions require educational innovations that can adapt learning processes to technological advancements without neglecting human values. This study aims to examine the concept of educational innovation in shaping a civil society in the era of disruption and Society 5.0. The research employed a qualitative method with a library research approach through the analysis of relevant journals, books, and other scientific sources. The findings indicate that educational innovation plays an important role in instilling values of tolerance, democracy, responbility, and social awareness, while also enhancing students critical thinking, creativity, collaboration, communication, and digital literacy skills. Therefore, educational innovation serves a crucial strat capable of addressing the challenges of the disruption era and Society 5.0.